Avian influenza overview February– August 2019. (27th September 2019) - ,; ,; ,; Adlhoch, Cornelia; Fusaro, Alice; Kuiken, Thijs; Monne, Isabella; Smietanka, Krzysztof; Staubach, Christoph; Muñoz Guajardo, Irene; Baldinelli, Francesca
Abstract : Between 16 February and 15 August 2019, five HPAI A(H5N8) outbreaks at poultry establishments in Bulgaria, two low pathogenic avian influenza (LPAI) A(H5N1) outbreaks in poultry in Denmark and one in captive birds in Germany, one LPAI A(H7N3) outbreak in poultry in Italy and one LPAI A(H7N7) outbreak in poultry in Denmark were reported in Europe. Genetic characterisation reveals that viruses from Denmark cluster with viruses previously identified in wild birds and poultry in Europe; while the Italian isolate clusters with LPAI viruses circulating in wild birds in Central Asia. No avian influenza outbreaks in wild birds were notified in Europe in the relevant period for this report. A decreased number of outbreaks in poultry and wild birds in Asia, Africa and the Middle East was reported during the time period for this report, particularly during the last three months. Furthermore, only six affected wild birds were reported in the relevant time period of this report. Currently there is no evidence of a new HPAI virus incursion from Asia into Europe. However, passive surveillance systems may not be sensitive for early detection if the prevalence or case fatality in wild birds is very low. Therefore, it is important to encourage and maintain passive surveillance in Europe encouraging a search for carcasses of wild bird species that are in the revised list of target species in order to detect any incursion of HPAI virus early and initiate warning. No human infections due to HPAI viruses ‐ detected in wild birds and poultry outbreaks in Europe ‐ have been reported during the last years and the risk of zoonotic transmission to the general public in Europe is considered very low.